Pengaruh Intensitas Bimbingan Orang Tua dan Sarana Prasarana Terhadap Motivasi Belajar Siswa Serta Implikasinya Pada Prestasi Belajar Siswa (Survei Pada Mata Pelajaran Kewirausahaan di Smk Ulil Albab Depok Kabupaten Cirebon) - Mokhammad Wahyudin (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2018)
The purpose of this study was to determine the effect of the intensity of parental guidance and infrastructure to the students' motivation and their implications for student achievement Smk Ulil Albab Cirebon Depok. The purpose of this study are: 1) To find a picture of student achievement, the intensity of parental guidance, facilities and students' motivation to learn; 2) To determine the effect intensity of parental guidance and infrastructure to student motivation and its implications on learning achievement. The method used is descriptive survey method verification. Data collected through questionnaires. In this study were used as the student population is Smk Ulil Albab Cirebon Depok many as 1556 people. The sample was 318 people. By using a sampling technique that is proportional random sampling. Based on the calculation and analysis of data, it can be concluded that: 1) Overview of learning achievement Students medium category, the intensity of parental guidance category is, the infrastructure category is, and student motivation sedang.2 category) there is a positive influence on the intensity of parental guidance and infrastructure on the students motivation. 3) There is no positive effect of the intensity of parental guidance on motivation to learn. 4) There is a positive effect of infrastructure study on motivation to learn. 5) There is no positive effect of the intensity of parental guidance, infrastructure and learning motivation on learning achievement. 6) There is no positive effect of the intensity of parental guidance on learning achievement. 7) There is no positive effect of infrastructure on student achievement. 8) There is no positive effect of learning motivation on student achievement.